EPA's Endocrine Disruptor Screening Program (EDSP) - Frederick M. Fishel (EDIS)
PI227, a 4-page fact sheet by F.M. Fishel, discusses EPA’s screening program for potential effects to the endocrine system caused by pesticide exposure. Includes additional sources of information. Published by the UF Department of Agronomy, April 2010.